The Impact of Top Management Ethical Climate, Ethical Leadership, and Firm Procedural Justice Climate on Organization Citizenship Behavior - Sidra Moid Khan; Salah ud Din Taj (iRASD Journal of Management)
This research aimed to investigate the influence of ethical leadership, ethical climate, and procedural justice on Organizational citizenship behavior (OCB) in the banking sector of Pakistan. And also search the role of OCB in affecting work outcomes. The sample population for the study was drawn from 220 employees working for several banks in Pakistan. The data collection will conduct through a structured survey questionnaire. Participants were exposed to task interdependence management and then rated the importance of OCB in the overall climate of the organization. The finding revealed that ethical leadership, ethical climate, and procedural justice were positively associated with collective OCB in the firm. Few conceptual studies and empirical views examined the relationship between leadership and OCB. This explanatory and quantitative research used convenient sampling techniques to support the hypothesis. The theoretical and managerial implications of the findings are discussed in the paper, together with some suggestions for managing leadership and OCB in the banking sector.